(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
The subject of our paper are idioms of three unrelated Balkan languages, Albanian, Greek and Serbian, that contain some of the key lexemes that nominate sweet ingredients or dessert. For the purpose of our paper, we shall refer to any such lexeme as the “sweet component”. We analyse such idioms and their translation equivalents from a semantic point of view in order to determine the similarities and differences they show with the traditional conceptualization of sweet flavour as something very pleasant and satisfying. Based on our results, it is concluded that the phraseological units with sweet component belong both to the positive and negative semantic field. In terms of their motivation, the sweet taste plays an important role when it comes to the phraseological units with positive connotation, while, on the other hand, it does not affect idiom formation with negative meaning.